Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1007/bf02365447
|View full text |Cite
|
Sign up to set email alerts
|

Small duct cholangitis induced byn-formyll-methioninel-leucinel-tyrosine in rats

Abstract: Primary sclerosing cholangitis (PSC) frequently accompanies inflammatory bowel diseases. In an attempt to increase our understanding of the pathogenesis of PSC, we studied bile duct changes in rats with colitis which had been given N-formyl L-methionine L-leucine L-tyrosine (fMLT) rectally; fMLT is one of the chemotactic peptides produced by Escherichia coli, and is secreted into the bile by hepatocytes after it enters the portal blood. Transrectal administration of fMLT induced a marked inflammation in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…fibrosis). 43,[45][46][47][48] Interestingly, these findings can be mitigated by antibiotic administration and by selective degradation of enteric bacterial components. 25,26 We believe that antibiotics such as metronidazole (effective against anaerobic bacteria) and vancomycin (effective against Gram-positive bacteria) may decrease the biosynthesis of bacterially derived immunoactive molecules and thus mitigate the aberrant (pro-inflammatory, pro-fibrotic) hepatobiliary immune responses and signalling cascades that they may trigger in immunogenetically susceptible individuals.…”
mentioning
confidence: 99%
“…fibrosis). 43,[45][46][47][48] Interestingly, these findings can be mitigated by antibiotic administration and by selective degradation of enteric bacterial components. 25,26 We believe that antibiotics such as metronidazole (effective against anaerobic bacteria) and vancomycin (effective against Gram-positive bacteria) may decrease the biosynthesis of bacterially derived immunoactive molecules and thus mitigate the aberrant (pro-inflammatory, pro-fibrotic) hepatobiliary immune responses and signalling cascades that they may trigger in immunogenetically susceptible individuals.…”
mentioning
confidence: 99%
“…A potential link between bacterial components and hepatobiliary inflammation was first substantiated by Chadwick and colleagues who demonstrated that N-formylated chemotactic peptides that are produced by several species of intestinal bacteria undergo enterohepatic circulation and that the levels of these compounds are increased in experimentally induced colitis [61][62][63]. In addition, rectal administration of N-formyl L-methionine L-leucine L-tyrosine in rats with acetate-induced colitis results in a biliary-based inflammation consisting of macrophages and neutrophils in the early stages and subsequently CD4+ and CD8+ T cells [64,65].…”
Section: Innate Immune Response In Pscmentioning
confidence: 87%
“…Of note, biliary inflammation may reflect abnormal immune responses to constituents of intestinal microorganisms, which do not necessarily require direct bacterial translocation to the biliary tree or portal circulation. For instance, proinflammatory peptides derived from colonic bacteria were sufficient to induce histological changes resembling PSC in rats with experimental colitis [100,101]. Such peptides trigger inflammation because they stimulate antimicrobial pattern recognition receptors, e.g., Toll-like receptors (TLR).…”
Section: Microbial Antigens In Aih and Pscmentioning
confidence: 99%